Identifying Substance Abuse Issues in High Schools: A National Survey of High School Counselors. - Burrow-Sanchez, Jason J.; Lopez, Adriana L. (Journal of Counseling & Development)
High school students consistently report the use of substances such as alcohol, cigarettes, and marijuana. One of the people they would talk to about a substance use problem is their school counselor. A survey study was conducted with a national sample of 289 high school counselors. Results indicated that participants were clearly able to identify their practice limitations and future training needs in this area. Implications for training and recommendations for future research are discussed. The magazine publisher is the copyright holder of this article and it is reproduced with permission. Further reproduction of this article in violation of the copyright is prohibited.